2016
DOI: 10.15326/jcopdf.3.1.2015.0128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Megestrol Acetate and Testosterone on Body Composition and Hormonal Responses in COPD Cachexia

Abstract: Background: Underweight chronic obstructive pulmonary disease (COPD) patients with involuntary weight loss have a poor prognosis; no effective therapy is currently available. We conducted the first clinical trial seeking to determine whether combination therapy with an appetite stimulant and an anabolic steroid would have beneficial effects on body composition for patients with COPD cachexia. Methods: We conducted a 12-week pilot study in which 4 men and 5 women (age 64±10 y, forced expiratory volume in 1 seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In the past few decades, various studies have demonstrated that androgens could exert anti-inflammatory and protective effects through direct or indirect effects in pulmonary diseases (6)(7)(8). Several randomized controlled trials (RCTs) investigated the influence of exogenous androgen therapy on body composition, muscle strength, exercise capacity and health-related quality of life (HRQoL) in patients with COPD (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, various studies have demonstrated that androgens could exert anti-inflammatory and protective effects through direct or indirect effects in pulmonary diseases (6)(7)(8). Several randomized controlled trials (RCTs) investigated the influence of exogenous androgen therapy on body composition, muscle strength, exercise capacity and health-related quality of life (HRQoL) in patients with COPD (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Cachexia is a multifactorial metabolic syndrome characterised by the dramatic loss of skeletal muscle mass, which is often accompanied by fat loss [ 1 ]. It is a devastating consequence seen in patients with acquired immune deficiency syndrome [ 2 ], burns [ 3 ], cancers [ 4 , 5 ], chronic obstructive pulmonary disease [ 6 ], chronic heart [ 7 ] and renal failures [ 8 ], diabetes [ 9 ], and sepsis [ 10 , 11 , 12 ]. During these disorders, the basal energy expenditure increases, which enhances the fat and protein catabolism primarily from the energy reserve organs and thus leads to wasting [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have included nutritional support and exercise without the addition of anabolic steroids (28,29,31) have found improvements in body weight, muscle strength, exercise performance and quality of life but no changes in FFM. Whereas the provision of megestrol acetate and testosterone alone in COPD patients with cachexia has been found to be associated with significant weight gain including both FM and FFM (50).…”
Section: Body Composition Improvements In Copdmentioning
confidence: 96%